Study on high-concentration activated sludge system for energy-efficient nitrogen removal in wastewater - Benfu Luo; Yuhang Liu; Yiqiang Huang; Weiwei Huang; Qiang Chen; Yujing Yan; Haixing He; Xiang Zhou; Jie Yu (Sustainable Environment Research)
Abstract Currently, there is an increasing emphasis on energy conservation and nitrogenous pollutant emission reduction, and conventional wastewater treatment processes can no longer meet the demand. Enhancing the reflux ratio of the mixed liquor suspended solids (MLSS) is a promising option to improve nitrogen removal in wastewater treatment. However, a high reflux ratio can lead to a significant carryover of dissolved oxygen (DO), which can negatively impact the denitrification process. Currently, eliminating the effects of DO remains a challenging area with high DO concentration inhibiting denitrification process. The high MLSS system can significantly reduce the impact of DO. Therefore, this study compares it with the conventional internal recirculation method in terms of pollutant removal and DO recovery. It explores the feasibility of using high MLSS system to enhance nitrogen removal in wastewater treatment while achieving energy savings, and calculates the potential energy savings achieved. At the same time, the biological tank reflux pump used by the air-lift pump exhibited more energy-saving advantages than the traditional mixture of liquid reflux pumps. This study focuses on wastewater treatment plants with poor denitrification performance, aiming to enhance denitrification efficiency. The results show that when the MLSS concentration is 8.0 g L−1 with the DO concentration 2.5 mg L−1, the system removed 97% of biochemical oxygen demand at influent 200 mg L−1, 86% of chemical oxygen demand (Cr method) at 350 mg L−1, 94% of ammonia nitrogen at 35 mg L−1, and 72% of total nitrogen at 45 mg L−1. This study can significantly reduce operating costs. The air-lift pump facilitates the lifting of wastewater, it also supplies DO to the water, thereby reducing the need for aeration. Compared to traditional recirculation methods, this approach saves approximately 32% of DO, resulting in an effective recovery, which notably enhances energy savings. However, it is important to note that the small scale of the bioreactor used in this experiment does not fully capture the advantages in energy saving and management that come with the implementation of a high MLSS system.